Metabolome and transcriptome integration explored the mechanism of browning in Glycyrrhiza uralensis Fisch cells - Zhao, Xinyang; Li, Xueshuang; Bao, Aodun; Zhang, Xiaoli; Xu, Yongbin; Li, Yali (Frontiers in Plant Science, 2024)
Glycyrrhiza uralensis Fisch, a traditional Chinese medicinal herb known for its diverse pharmacological effects including heat-clearing, detoxification, phlegm dissolving, and cough relief, has experienced an exponential increase in demand due to its expanding clinical use and development prospects. Currently, large-scale cell culture stands out as one of the most promising biotechnological approaches for producing bioactive compounds from medicinal plants. However, the problem of cell browning represents a significant bottleneck in industrial applications of cell culture. This study focuses on the Glycyrrhiza uralensis Fisch cells from the Ordos plateau, aiming to elucidate the enzymatic browning process during plant cell culture. Key substrates and genes involved in enzymatic browning were identified by metabolome and transcriptome analysis of normal and browning cells. Metabolome analysis reveals significant changes in the levels of chalcone, isoflavone, imidazole-pyrimidine, purine nucleosides, organic oxides, carboxylic acids and their derivatives, benzene and its derivatives, flavonoids, 2-arylated benzofuran flavonoids, diazanaphthalenes and fatty acyls within browning cells. In particular, chalcones, isoflavones, and flavones compounds account for a higher proportion of these changes. Furthermore, these compounds collectively show enrichment in four metabolic pathways: Isoflavone biosynthesis pathway; Cutin suberine and wax biosynthesis pathway; Aminoacyl-tRNA biosynthesis pathway; Isoquinoline alkaloid biosynthesis pathway; Transcriptome analysis revealed that the MYB transcription factor is a key regulator of flavonoid synthesis during the browning process in cells. In addition, 223 differentially expressed genes were identified, including phenylpropane, shikimic acid, glycolysis, and pentose phosphate pathways. Among these genes, 23 are directly involved in flavonoid biosynthesis; qPCR validation showed that eight genes (GlPK, GlPAL, Gl24CL, Gl1PDT, Gl3CHI, GlC4H, Gl2F3'H, and Gl2CCR) were up-regulated in browning cells compared to normal cells. These findings corroborate the sequencing results and underscore the critical role of these genes in cellular browning. Consequently, modulation of their expression offers promising strategies for effective control of cellular browning issues.